SDIR Mathematical Approach with Time Delay Factor to Reveal Indonesian Students' Interest in Government Organizations and Internships: A Case in FMIPA UNM - Side, Syafruddin; Sanusi, Wahidah; Yusuf S.A.P., Andi Muh. Ridho (Journal of Mathematics: Theory and Applications, 2024)
This study is to build a time-delay SDIR model on the case of student interest in Organizations and Government Internship Programs, analyze the model and conduct a model simulation to predict the level of student interest cases in Organizations. This study is a theoretical and applied study. Analysis of the time-delay SDIR model of the case of student interest in Organizations, while the model simulation uses Maple Software. The population of the study was active students of FMIPA UNM, with a sample size of 1029 students obtained using the Sloving technique. The results of this study are a mathematical model of SDIR on the case of student interest in Organizations which is a system of differential equations. The model analysis provides a value of the free equilibrium point of the case of student interest in Organizations and a stable endemic equilibrium point. The results also found that the basic reproduction number value for cases without a solution would produce R0n = 9.912507841, which means that in social cases where one individual can influence 9-10 people in their environment to hesitate to participate in organizational activities or internship programs, but on the other hand if the case is given a solution, it will produce R0s = 0.2737372211, which means that there is no psychological spread, where each individual does not influence other individuals.